2014
DOI: 10.1038/bonekey.2014.97
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of abnormal bone composition in vivo using noninvasive Raman spectroscopy

Abstract: X-ray-based diagnostic techniques, which are by far the most widely used for diagnosing bone disorders and diseases, are largely blind to the protein component of bone. Bone proteins are important because they determine certain mechanical properties of bone and changes in the proteins have been associated with a number of bone diseases. Spatially Offset Raman Spectroscopy (SORS) is a chemically specific analytical technique that can be used to retrieve information noninvasively from both the mineral and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…The assessment would however be restricted to superficial areas, due to the (very) low penetration depth of light in hard tissues such as bone. For instance, it has been shown that Raman spectroscopy can be performed on bone transcutaneously [88,89,94,95], whereas application of SHG in vivo in tissues underneath the skin is possible through the use of endomicroscopes [294,295], which can in addition preserve the laser polarization and, thus, also enable pSHG imaging [296,297]. Therefore, the use of PRS and ( p)SHG for the in vivo assessment of the ultrastructural organization of bone can be envisaged in the future.…”
Section: In Vivo Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment would however be restricted to superficial areas, due to the (very) low penetration depth of light in hard tissues such as bone. For instance, it has been shown that Raman spectroscopy can be performed on bone transcutaneously [88,89,94,95], whereas application of SHG in vivo in tissues underneath the skin is possible through the use of endomicroscopes [294,295], which can in addition preserve the laser polarization and, thus, also enable pSHG imaging [296,297]. Therefore, the use of PRS and ( p)SHG for the in vivo assessment of the ultrastructural organization of bone can be envisaged in the future.…”
Section: In Vivo Assessmentmentioning
confidence: 99%
“…This is often combined with composition analysis [90,91], which is an inherent capability of Raman spectroscopes to provide properties that determine different bone quality [92] and other clinically relevant [88,93] properties. Because of the attention Raman spectroscopy has been gaining as an in vivo imaging modality [88,89,94,95], and the advances that have been made in recent years in the tools to characterize mineralized collagen fibril orientation, Raman spectroscopy/imaging can be expected to become a common tool to characterize bone ultrastructure organization in the near future.…”
Section: Polarized Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…This is a major drawback as it has been shown that collagen plays an essential role in determining the structural properties of the bone matrix. 1,2 In addition, ionizing radiation can become an issue if radiation exposure accumulates after numerous scans (not uncommon to monitor the effects of pharmaceutical treatment of bone conditions, as e.g. bisphosphonates prescribed in the case of osteoporosis).…”
Section: Introductionmentioning
confidence: 99%
“…Application areas include the identification of breast calcifications 4 and the detection of tumors 5 . Intensive research has also been performed on transcutaneous bone characterization to assess material composition for potential bone disease diagnosis [6][7][8] . Despite these successes, a key issue remains largely unaddressed: from what depth Raman information is extracted for a given spatial offset and how does the light scattering properties of tissues influence the SORS process at the applied NIR wavelengths?…”
Section: Introductionmentioning
confidence: 99%